Infection with Kapsulotaenia sandgroundi (Carter, 1943) in Komodo Dragons (Varanus komodoensis Ouwens, 1912) on Rinca Island, East Nusa Tenggara, Indonesia - Winarso, Aji; Maha, Inggrid Trinidad; Wuhan, Yustinus Oswin Primajuni; Nurcahyo, Raden Wisnu; Priyowidodo, Dwi; Foitová, Ivona (ARSHI Veterinary Letters, 2024)
This article describes the infection with Kapsulotaenia sangroundi (Carter, 1943) in the komodo dragon (Varanus komodoensis Ouwens 1912) at Loh Buaya on Rinca Island, Komodo National Park. A newly dropped dragon faeces sample was collected and preserved in the SAF solution. Native parasitic examination was performed under a microscope (40x objective magnification). Environmental observations were performed to obtain additional information on the life cycle and transmission of the parasite. Observation of faecal samples revealed the presence of cestode eggs in the egg packaging (capsules). One of the five samples showed a positive result (20%). The life cycle of Kapsulotaenia is intricate and highlights the importance of understanding the parasitic relationships in ecosystems. Understanding this infection is crucial for the conservation and management of Komodo dragons, as it highlights the need for monitoring health issues in their natural habitat.